Curcumin Ameliorates White Matter Injury after Ischemic Stroke by Inhibiting Microglia/Macrophage Pyroptosis through NF-κB Suppression and NLRP3 Inflammasome Inhibition. (30th September 2021) - Ran, Yuanyuan; Su, Wei; Gao, Fuhai; Ding, Zitong; Yang, Shuiqing; Ye, Lin; Chen, Xuechai; Tian, Guiqin; Xi, Jianing; Liu, Zongjian
Abstract : NLRP3 inflammasome-mediated pyroptosis is a proinflammatory programmed cell death pathway, which plays a vital role in functional outcomes after stroke. We previously described the beneficial effects of curcumin against stroke-induced neuronal damage through modulating microglial polarization. However, the impact of curcumin on microglial pyroptosis remains unknown. Here, stroke was modeled in mice by middle cerebral artery occlusion (MCAO) for 60 minutes and treated with curcumin (150 mg/kg) intraperitoneally immediately after reperfusion, followed by daily administrations for 7 days. Curcumin ameliorated white matter (WM) lesions and brain tissue loss 21 days poststroke and improved sensorimotor function 3, 10, and 21 days after stroke. Furthermore, curcumin significantly reduced the number of gasdermin D + (GSDMD + ) Iba1 + and caspase-1 + Iba1 + microglia/macrophage 21 days after stroke. In vitro, lipopolysaccharide (LPS) with ATP treatment was used to induce pyroptosis in primary microglia. Western blot revealed a decrease in pyroptosis-related proteins, e.g., GSDMD-N, cleaved caspase-1, NLRP3, IL-1 β, and IL-18, following in vitro or in vivo curcumin treatment. Mechanistically, both in vivo and in vitro studies confirmed that curcumin inhibited the activation of the NF- κ B pathway. NLRP3 knocked down by siRNA transfection markedly increased the inhibitory effects of curcumin on microglial pyroptosis and proinflammatory responses, both in vitro and in vivo . Furthermore, stereotaxic microinjection of AAV-based NLRP3 shRNA significantly improved sensorimotor function and reduced WM lesion following curcumin treatment in MCAO mice. Our study suggested that curcumin reduced stroke-induced WM damage, improved functional outcomes, and attenuated microglial pyroptosis, at least partially, through suppression of the NF- κ B/NLRP3 signaling pathway, further supporting curcumin as a potential therapeutic drug for stroke.